Development of alternative dispute resolution in the Iranian construction industry - Saeb, Abdollah; Mohamed, Othman; Danuri, Mohd Suhaimi Mohd; Zakaria, Norhanim (Construction Research Institute of Malaysia, 2018)
The purpose of this paper is to investigate and development of Alternative Dispute Resolution (ADR) methods in the Iranian construction industry. ADR methods were developed to acquire suitable solutions. From the research findings, despite the existence of laws for ADR methods, ADR has not been developed in Iran, and the infrastructures are not available for its development. Therefore, the Litigation process remains the main method of resolving disputes. If ADR is developed, it can be effective in resolving disputes in the construction industry and yield positive results. The potential of binding methods of ADR for dispute resolution in the construction industry is about 2.25 times that of non-binding methods. Mixed Method and Concurrent Triangulation Strategy have been used to carry out the investigations. The qualitative data collected for this research was through semi-structured interviews with 30 experts, and the quantitative data was collected through questionnaires with 112 experts.